2021
DOI: 10.1136/bcr-2021-245397
|View full text |Cite
|
Sign up to set email alerts
|

Complex auditory musical hallucinations with ambivalent feelings

Abstract: A 78-year-old woman with hypertension, diabetes mellitus type 2 and bilateral sensorineural hearing loss was referenced to geriatric psychiatry consultation. She presented cognitive dysfunction, erotomanic delusion and complex musical hallucinations (MH), described as hearing her neighbour singing a familiar church song along with bells in the background, making comments and talking to her. A computed tomography (CT) of the brain detected small right nucleocapsular and bilateral external capsules hypodensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…This lack of insight may extend to their musical hallucinations, making it difficult for them to recognize these perceptions as hallucinatory in nature, and encouraging secondary delusions. This was also the case with two of the three patients mentioned in the introduction, who likewise reacted to their musical hallucinations with paranoid delusions ( 18 , 19 ). There are also published cases where neurodegenerative disorders such as Alzheimer’s disease and Lewy body dementia led up to a misattribution of the origin of musical hallucinations [e.g., ( 19 , 34 )].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This lack of insight may extend to their musical hallucinations, making it difficult for them to recognize these perceptions as hallucinatory in nature, and encouraging secondary delusions. This was also the case with two of the three patients mentioned in the introduction, who likewise reacted to their musical hallucinations with paranoid delusions ( 18 , 19 ). There are also published cases where neurodegenerative disorders such as Alzheimer’s disease and Lewy body dementia led up to a misattribution of the origin of musical hallucinations [e.g., ( 19 , 34 )].…”
Section: Discussionsupporting
confidence: 52%
“…For example, Bieler et al ( 16 ) described a 92-year-old cognitively intact woman with hearing impairment and musical hallucinations who called the police because “her neighbors refused to turn off the music.” The hallucinations disappeared after a plug of cerumen and wool had been removed from her right ear, and they were attributed to the auditory Charles Bonnet syndrome, a variant of musical hallucinosis due to hearing loss ( 17 ). Another published case involves a 78-year-old woman with hearing loss, cognitive dysfunction, erotomanic delusions, and complex musical hallucinations, who heard her neighbor singing a familiar church song that was interrupted by provocative and sexually laden comments ( 18 ). The authors diagnosed her with dementia with psychotic symptoms, which reduced slightly with a combined treatment with clozapine, zonisamide, donepezil, and memantine.…”
Section: Introductionmentioning
confidence: 99%
“…The largest and most recent review of 393 cases of MH identified five categories of associated comorbid conditions: neurological, psychiatric, structural, drug effect, and not otherwise classifiable [ 4 ]. Some studies report MH in 0.16% of general psychiatric admissions and up to 2.5% of elderly patients with hearing impairment or other neurodegenerative disorders [ 3 , 5 , 7 ]. Over the years researchers have continued to study the prevalence of MH in order to better understand its epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic features described by patients may shine a light on potential underlying causes of AH. Psychotic spectrum disorders, such as schizophrenia, more commonly present with auditory hallucinations that are verbal in nature [ 3 , 4 ]. Often referred to as “command” hallucinations with voices speaking in the second or third person.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation